NILAI-NILAI PENDIDIKAN PESANTREN SEBAGAI CORE VALUE; DALAM MENJAGA MODERASI ISLAM DI INDONESIA - Dakir, Dakir; Anwar, Harles (JURNAL ISLAM NUSANTARA, 2019)
Antroplogically, the portrait of the presence of pesantren, as the oldest Islamic educational institution in Indonesia, has significantly demonstrated its kirpah in the community, both as a socio-religious institution and as an educational institution. This view, of course, cannot be separated from the value system established by the founders of the pesantren based on the Qur'an and al-Hadith, so that the values of local wisdom are in accordance with the social conditions of a pluralistic Indonesian society. Therefore, the internalization of social values above is expected to be a basic value in maintaining Islamic moderation in Indonesia, accordingly with the vision of Islam rahmatan lil'alamin, so that it can bring world peace. In this context, the habitualization of pesantren values becomes the root of social culture and has transcended its time (transculturation) so that the value system in question gives birth to a portrait of moderate Islamic education. Thus the internalization of these values, becomes (social capital) for pesantren to build and maintain Islamic moderation. Therefore, pesantren education is in essence, always in touch with the social reality that surrounds it (historical determinism and practical realism), this view can then give birth to a moderate Islamic education paradigm believed to be socio-cultural enlightenment, by promoting the principle of togetherness (ijtima'iyyah) , justice, tolerance (tasamuh) consultation (shura), towards social liberation so as to realize polite and childbirth (ukhuwah islamiyyah, wataniyyah, and insaniyah) in accordance with the vision of Islam rahmatan lil'alamain.